Acquired Incarcerated Inguinal Hernia: A Review of 13 Horses - Weaver, A. David (1987)
The case records of 13 horses with acquired incarcerated inguinal hernia in January-August 1983, were reviewed. Nine cases were in stallions. The remaining four involved eventration 5-48 hours following castration. Ages ranged from 1-17 years. Horses showed a variable degree of colic. Bowel was felt to pass through the internal inguinal ring on rectal examination in most cases. The physical features of the scrotum varied considerably. Resection of ischemic jejunum and/or ileum was necessary in three horses. Two horses were euthanized at surgery (one with bilateral ischemic jejunum, one with bowel perforation), and a further horse on day 16 postsurgery following development of multiple adhesions. All stallions were castrated. Follow-up for 6-24 months (mean 12.7) disclosed that all ten discharged horses were alive and healthy (recovery rate 77%).